PESTISIDA NABATI DAUN BABADOTAN (Ageratum conyzoides L.) DALAM MENGENDALIKAN HAMA PADA TANAMAN PAKCOY (Brassica rapa L.) - Siti Maisyaroh; Noorkomala Sari; Akhmad Rizali (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2025)
Demand for pak choi plants has continued to increase in recent years, but due to pest attacks, it has caused unstable production of pak choi plants. The main pests that attack pak choi plants are armyworms and caterpillars. One way to control pests on pak choi plants is to use organic-based biopesticide that are safer to use. One of the organic materials that can be used for organic pesticides is goat weed leaves. Goat weed is a nuisance weed that lives wild and is found in many regions in Indonesia. Goat weed plants can be used as biopesticide because goat weed plants have bioactive content that is anti-pest. The factor studied in this. research is the treatment of goat weed leaf extract with five concentration levels repeated as many as four replicates so as to get 20 units of experimental units. The results obtained from this study are pests that attack pak choi plants in this study are armyworms, tritip caterpillars, and flea beetles. Application of botanical pesticide solution of goat weed leaves has an effect on pest control in pak choi plants. The best concentration in the application of goat weed leaves solution is at a concentration of 20%, namely with a value of pest attack intensity on pak choi of 3.1%.